TLBfind: a Thermal Lattice Boltzmann code for concentrated emulsions with FINite-size Droplets - Pelusi, Francesca; Lulli, Matteo; Sbragaglia, Mauro; Bernaschi, Massimo (Computer Physics Communications, 2022)
In this paper, we present TLBfind, a GPU code for simulating the hydrodynamics of droplets along with a dynamic temperature field. TLBfind hinges on a two-dimensional multi-component lattice Boltzmann (LB) model simulating a concentrated emulsion with finite-size droplets evolving in a thermal convective state, just above the transition from conduction to convection. The droplet concentration of the emulsion system is tunable and at the core of the code lies the possibility to measure a large number of physical observables characterising the flow and droplets. Furthermore, TLBfind includes a parallel implementation on GPU of the Delaunay triangulation useful for the detection of droplets' plastic rearrangements, and several types of boundary conditions, supporting simulations of channels with structured rough walls. Program summary: Program Title: TLBfind CPC Library link to program files: https://doi.org/10.17632/hbk45696nf.1 Developer's repository link: https://github.com/FrancescaPelusi/TLBfind Licensing provisions: MIT Programming language: CUDA-C Nature of problem: Hydrodynamics of concentrated emulsions with finite-size droplets in a thermal convective state. Solution method: Single relaxation time Lattice Boltzmann method to solve Navier-Stokes equations for fluids, coupled with the temperature field dynamics. The output describes the dynamics of finite-size droplets of concentrated emulsions in presence of a temperature field. The temperature field obeys the advection-diffusion equation. Additional comments including restrictions and unusual features: Plastic rearrangements of droplets are detected via the parallel implementation of the Delaunay triangulation, and boundary conditions are tunable.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Finite-size droplets; Lattice Boltzmann; Rough channels; Soft suspensions; Thermal convection